Reallocating children's time: Coping strategies after the 2010 Haiti earthquake - Rafael Novella; Claire Zanuso (IZA Journal of Development and Migration, 2018)
This paper estimates the impact of the 2010 Haiti earthquake on the household decision about children's time allocation. Using original data and objective geological measures, we exploit the fact that the earthquake might affect the decision about children's time through its magnitude and household's revealed vulnerability. Separated measures of the earthquake magnitude and its damage allow us to estimate the impact of the household's vulnerability on the decision about the time allocation of children 10 to 17 years old. We are also able to analyze the differentiated effect on market and domestic work. Our results show that vulnerability at the time of the earthquake severely affects investments in children's human capital almost 3 years after the shock, which increases the household's risk of staying in poverty.
Keywords: J13; J22; O54; P46; Q54; 330; Child labor; School attendance; Natural disasters; Haiti